Analysis of long-term structural failure after native tissue prolapse surgery: a 3D stress MRI-based study - Chen, Luyun; Schmidt, Payton; DeLancey, John O.; Swenson, Carolyn W. (International Urogynecology Journal, 2022)
Introduction and hypothesis We sought to identify postoperative structural failure sites associated with long-term prolapse recurrence and their association with symptoms and satisfaction. Methods Women who had a research MRI prior to native-tissue prolapse surgery were recruited for examination, 3D stress MRI, and questionnaires. Recurrence was defined by Pelvic Organ Prolapse Quantification System (POP-Q)Ba/Bp > 0 or C > -4. Measurements were performed at rest and maximum Valsalva (“strain”) including vaginal length, apex location, urogenital hiatus (UGH), and levator hiatus (LH). Measures were compared between subjects and to women with normal support. Failure frequency was the proportion of women with measurements outside the normal range. Symptoms and satisfaction were measured using validated questionnaires. Results Thirty-one women participated 12.7 years after surgery—58% with long-term success and 42% with recurrence. Failure site comparisons between success and failure were: impaired mid-vaginal paravaginal support (62% vs. 28%, p = 0.01), longer vaginal length (54% vs. 22%, p = 0.03), and enlarged urogenital hiatus (54% vs. 22%, p = 0.03). Apical paravaginal location had the lowest failure frequency (recurrence: 15% vs. success: 7%, p = 0.37). Patient satisfaction was high (recurrence: 5.0 vs. success: 5.0, p = 0.86). Women with bothersome bulge symptoms had a 33% larger UGH strain on POP-Q ( p = 0.01), 8.7% larger resting UGH ( p = 0.046), 11.5% larger straining LH ( p = 0.01), and 9.3% larger resting LH ( p = 0.01). Conclusions Abnormal low mid-vaginal paravaginal location (Level II), long vaginal length (Level II), and large UGH (Level III) were associated with long-term prolapse recurrence. Patient satisfaction was high and unrelated to anatomical recurrence. Bothersome bulge symptoms were associated with hiatus enlargement.